A STRUCTURAL EQUATION MODEL OF A LEAN PRODUCTION SYSTEM, QUALITY OF WORK LIFE, AND ORGANIZATIONAL PERFORMANCE OF THE AUTO PARTS INDUSTRY IN THAILAND - Apiwat Krommuang; Opal Suwunnamek (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to analyze a structural equation model of a lean production system and quality of work-life affecting the organizational performance of auto parts businesses in Thailand. The conceptual framework was taken from reviewed literature to determine the mentioned variables on their direct, indirect and total effects on organizational performance. 520 respondents comprising top and middle managers from auto parts businesses in Thailand were randomized by purposive sampling. SPSS and AMOS programs were used as analysis tools. The results showed that a lean production system had a significant and direct effect on quality of work-life and organizational performance. In addition, it had a significant indirect effect on organizational performance through the quality of work-life.